Management Behavior Of Rabies-Transmitting Animal (Rta) Bites In The Work Area Of Kawua Health Centre, Poso Regency - Firmansyah Firmansyah; Rahma Rahma; Rasyika Nurul Fadjriah; Lusia Salmawati (Journal of Health and Nutrition Research, 2022)
The Kawua Health Center is one of the health centers in Poso Regency with the highest rabies-transmitting animal (RTA) bite cases in 2019 and is very disturbing to the community. Bites of Rabies Transmitting Animals (RTA) are risky for transmitting the rabies virus to humans, so an effective and efficient response is needed. The purpose of the study was to obtain information on the behavior of handling Rabies Transmitting Animal Bites in the working area of ​​the Kawua Health Center, Poso Regency. Data collection was done by in-depth interviews involving 15 research informants determined by the purposive sampling technique. The results showed that the informants' knowledge was still not good regarding rabies, both in terms of prevention and control of RTA bites. The attitude of the informant was not good in carrying out first aid measures and prevention efforts before RTA bites occurred. Also, the role of health workers was not good in preventing and controlling rabies cases in the working area of ​​the Kawua Health Center. Families play an important role in controlling rabies by providing informational, emotional, and instrumental support. It is recommended for the Kawua Health Center staff to improve the prevention and control of RTA bites cases further